The Muscular Dystrophies - Flanigan, Kevin M. (Seminars in Neurology, 2012)
The muscular dystrophies are disorders of progressive muscular degeneration and weakness. As a group they display clinical heterogeneity that reflects the heterogeneity of molecular mechanisms responsible for them, and range from congenital to adulthood onset. Recent advances in the field include improved methods of diagnosis, continued identification of disease genes, and the development of a unified model of pathogenesis in facioscapulohumeral dystrophy. These advances are reflected in the development of new therapeutic approaches, some of which have already led to clinical trials in the dystrophinopathies and limb-girdle dystrophies.
Keywords: muscular dystrophy; dystrophinopathy; facioscapulohumeral; limb-girdle